2009
DOI: 10.2174/156652409788488793
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Molecular Approaches to the Immunopathogenesis of Multiple Sclerosis: An Update

Abstract: Although the aetiology of MS remains elusive, several genetic approaches have provided clues to the underlying molecular pathogenesis. In addition to the well known association to HLA class II alleles, weak but highly significant association to the interleukin-7 receptor and interleukin-2 receptor genes has recently been established. A series of other promising candidate genes identified in large genome screens are under evaluation. The genetic predisposition to MS is so far shown to be mediated by common poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 257 publications
(326 reference statements)
0
4
0
2
Order By: Relevance
“…However, even for the well‐established effect of the human leucocyte antigen (HLA) DRB1*1501 class II allele [13], the predicted contribution on MS genetics appears to be modest [12,13,69]. Recently, the genome‐wide association methodology and large studies using the classic candidate‐gene approach have identified SNPs (interleukin‐2 receptor A on chromosome 10 and interleukin‐7 receptor A on chromosome 5) located outside the MHC gene region that were related to MS [11,70–75]. Once again, the mutant alleles explained only a small fraction of the variance in the risk of the development of MS [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even for the well‐established effect of the human leucocyte antigen (HLA) DRB1*1501 class II allele [13], the predicted contribution on MS genetics appears to be modest [12,13,69]. Recently, the genome‐wide association methodology and large studies using the classic candidate‐gene approach have identified SNPs (interleukin‐2 receptor A on chromosome 10 and interleukin‐7 receptor A on chromosome 5) located outside the MHC gene region that were related to MS [11,70–75]. Once again, the mutant alleles explained only a small fraction of the variance in the risk of the development of MS [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the genome-wide association methodology and large studies using the classic candidate-gene approach have identified SNPs (interleukin-2 receptor A on chromosome 10 and interleukin-7 receptor A on chromosome 5) located outside the MHC gene region that were related to MS [11,[70][71][72][73][74][75]. Once again, the mutant alleles explained only a small fraction of the variance in the risk of the development of MS [11].…”
Section: Discussionmentioning
confidence: 99%
“…Die Bedeutung des B-Zell-Arms für die Pathogenese der MS rückt ebenfalls in den Fokus (14,27). Obwohl die genauen Ursachen, die zur Störung der Schrankenfunktion des Endothels führen, noch unklar sind, werden verschiedene infektiöse und genetische Mechanismen diskutiert, die zur remittierenden Entzündungsreaktion führen können (13,19,40). Die Kontrolle dieser Entzündungsreaktionen und ihrer lokalen Komplikationen stellt damit die wichtigste therapeutische Intervention für die MS dar.…”
Section: Discussionunclassified
“…MS is believed to be caused by a combination of factors including genetic susceptibility, gender and environmental influences such as toxins or bacterial/viral infection [15][16][17]. The typical demyelination of tissue plaques goes along with a complex neuro pathology that includes axonal degeneration, the invasion of activated autoantigen-specific T lymphocytes into the central nervous system, astrogliosis, microglial activation, alterations regarding several molecular networks including chemokines and cytokines and autoantibodies directed against myelin components [18][19][20].…”
Section: White Matter Disorders: Leukodystrophies and Multiple Sclerosismentioning
confidence: 99%
“…The typical demyelination of tissue plaques goes along with a complex neuro pathology that includes axonal degeneration, the invasion of activated autoantigen-specific T lymphocytes into the central nervous system, astrogliosis, microglial activation, alterations regarding several molecular networks including chemokines and cytokines and autoantibodies directed against myelin components [18][19][20]. It is of note, however, that the established MS-susceptibility genes of the major histocompatibility complex as well as those with weaker associations [21,22,15] are not 'myelin genes' but 'immune genes'. …”
Section: White Matter Disorders: Leukodystrophies and Multiple Sclerosismentioning
confidence: 99%